Intermolecular Coulombic Decay in Endohedral Fullerene at the 4d→4f Resonance - Obaid, Razib; Xiong, Hui; Augustin, Sven; Schnorr, Kirsten; Ablikim, Utuq; Battistoni, Andrea; Wolf, Thomas J. A.; Bilodeau, René C.; Osipov, Timur; Gokhberg, Kirill; Rolles, Daniel; LaForge, Aaron C.; et al. (My University, 2020)
Intermolecular processes offer unique decay mechanisms for complex systems to internally relax. Here, we report the observation of an intermolecular Coulombic decay channel in an endohedral fullerene, a holmium nitride complex (Ho3N) embedded within a C80 fullerene, between neighboring holmium ions, and between the holmium complex and the carbon cage. By measuring the ions and the electrons in coincidence after XUV photoabsorption, we can isolate the different decay channels, which are found to be more prevalent relative to intra-atomic Auger decay.